Faktor-Faktor yang Mempengaruhi Minat Belajar Peserta Didik Asli Papua terhadap Mata Pelajaran Matematika - Mayor M. H. Manurung; Pitriana Tandililing (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
This research aims to describe what factors influence the interest of native Papuan students in mathematics subjects at SMP Negeri 11 Jayapura, especially in class VII. The results of the research show that the learning interest of native Papuan students in class VII of SMP Negeri 11 Jayapura towards mathematics subjects is still low, namely around 50.09%. Students who like mathematics are influenced by several factors, namely: (1) Students have an interest in learning mathematics because they consider mathematics to be fun and enjoyable; (2) Students have the motivation to study mathematics because they consider mathematics to be important to support their dreams and future work; (3) the teacher is friendly and kind explanation is easy to understand; (4) A comfortable learning atmosphere both at school and at home; (5) Family who supports learning mathematics; and (6) Friends who support learning mathematics. Meanwhile, students who do not like mathematics are influenced by several factors, namely: (1) Students do not have interest in learning mathematics because they think mathematics is a difficult subject because there are many formulas and calculations; (2) Students do not have the motivation to learn mathematics; (3) Explanation teachers are difficult to understand; (4) they have not liked mathematics lessons since they were in elementary school; (5) Parents do not support students in learning mathematics; (6) Students do not have a study group at home; and (7) Students often play on cellphones at home. However, all subjects (100%) considered mathematics to be an important and useful subject for their future.